Association analysis of single-nucleotide polymorphism in prolactin and its receptor with productive and body conformation traits in Liaoning cashmere goats - Y. Wu (Archives Animal Breeding, 2022)
The results of this study showed that the single-nucleotide polymorphism (SNP) sites of the PRL and PRLR genes have a certain association with the milk production performance, body size and cashmere performance of Liaoning cashmere goats (LCGs). Through our designed experiment, the potential SNPs of LCG were detected by sequence alignment, and two SNPs were found on two genes. The CC genotype of the PRL gene is the dominant genotype among the three genotypes. The GG genotype of the PRLR gene is the dominant genotype among the two genotypes. At the same time, the two genotypes also have good performance in cashmere production and body size. Through the screening of haplotype combination, the milk fat rate > 7.6 %, the milk protein rate > 5.6 %, the milk somatic cell number < 1500 × 103 mL−1, the cashmere fineness < 15.75 µm, the chest girth > 105 cm, the chest depth > 33 cm, and the waist height > 67.5 cm are considered as screening indexes for comprehensive production performance of Liaoning cashmere goats. It is concluded that the GCGC type is the dominant haplotype combination. According to our research data, we found that the biological indicators of Liaoning cashmere goat milk are higher than the national standards, so we think it is very significant to study the milk production performance of our experiment. Further research can be done on goat milk production and body conformation traits around PRL gene and PRLR gene.